Application of Digital Leadership in Establishing Sustainable Competitive Advantage against MSMEs in Denpasar City in the future Covid-19 (Implementation of Digital Leadership in forming Sustainable Competitive Advantage on MSME in the city of Denpasar during Covid-19) - I Putu Dharmawan Pradhana; Anak Agung Istri Agung Maheswari; Nyoman Sri Manik Parasari; Ida Ayu Parwati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Covid-19 pandemic has forced MSMEs to change their situation and situation from conventional to online or everything using digital technology, this has an impact on the three MSMEs, namely Donat Chatis, Griya Florist, and Gangs Studio which researchers want to research need the role of digital leadership in forming a competitive advantage that is different from other competitors by knowing the strengths, weaknesses, opportunities, and threats that exist in the three MSMEs to be able to survive in the era of the industrial revolution 4.0, especially during the time of covid-19. Where the research method in this writing uses the Qualitative Method with Source Data primary and secondary, informant study which obtained direct dai third owners, employee, and customer from MSME Donuts chat, Griya Florist, and Gangs Studio. Instruments study qualitative this which Becomes instrument or the research tool is the researcher himself. Data collection techniques are obtained by observation, interviews, and Documentation. Data analysis techniques are used starting from data collection, data reduction, presentation data, and withdrawal conclusion/verification. Techniques for data validity through data triangulation, namely source triangulation, technical triangulation, and data triangulation time and location study on 3 MSMEs which there in City Denpasar is MSME Donuts chatis, Griya florist, and Gangs Studio. The results of this study are based on the results of data analysis, it can be concluded that the application of swot analysis and the application of digital leadership in the three MSMEs is fairly simple in concept and implementation. Three attempts this no want to make Thing complicated in internal his efforts as well management HR which owned. Things could be seen from several aspects, for example, employee development and monitoring methods, employee service to customers, harmonization Between leader and employee, as well as results product generated through creativity leader and employee direct.